Palladium-Catalyzed Molybdenum Hexacarbonyl-Mediated Gas-Free Carbonylative Reactions - Åkerbladh, Linda; Odell, Luke R.; Larhed, Mats (Synlett, 2019)
This account summarizes Pd(0)-catalyzed Mo(CO)6-mediated gas-free carbonylative reactions published in the period October 2011 to May 2018. Presented reactions include inter- and intramolecular carbonylations, carbonylative cross-couplings, and carbonylative multicomponent reactions using Mo(CO)6 as a solid source of CO. The presented methodologies were developed mainly for small-scale applications, avoiding the problematic use of gaseous CO in a standard laboratory. In most cases, the reported Mo(CO)6-mediated carbonylations were conducted in sealed vials or by using two-chamber solutions.1 Introduction2 Recent Developments2.1 New CO Sources2.2 Two-Chamber System for ex Situ CO Generation2.3 Multicomponent Carbonylations3 Carbonylations with N and O Nucleophiles4 Carbonylative Cross-Coupling Reactions with Organometallics5 Carbonylative Cascade Reactions6 Carbonylative Cascade, Multistep Reactions7 Summary and Outlook
Keywords: carbonylation; molybdenum; multicomponent reactions; palladium; catalysis